Effects of the protonation and the polar solvation on the molecular properties of methyl orange: A density functional theory study - You, Kanghyeon; Kwon, O. Pil; Kim, Dongwook (Bulletin of the Korean Chemical Society, 2023)
Methyl orange (MO) and its protonated derivatives were investigated at the density functional theory (DFT) level using CAM-B3LYP functional and 6-311 + G(d,p) basis sets; their absorption spectra in aqueous solution were simulated, their relative stabilities in both the gas phase and the polar solutions were calculated, and the activation energy barrier for the cis-to-trans isomerization in both phases were computed. Except the protonation at the amino group, all the protonated isomers show a bathochromic shift of the most intense absorption peak. In the gas phase, the sulfonate unit turns out to be the most favorable proton acceptor. In the polar solutions, however, azo groups are more effective to accept the proton. The protonation at the azo N atom next to the phenyl-sulfonate group significantly reduces the energy barrier for the cis-to-trans conversion in the aqueous solution, which suggests a swift conversion in the ground state.
Keywords: Cis-to-trans isomerization; Density functional theory studies; Gas-phases; Methyl Orange; Protonated; Protonations; The solvation effect; Zwitterionic interaction; Zwitterionics; cis-to-trans isomerization; DFT study; methyl orange; the solvation effect; zwitterionic interactions